Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres) - Eisenhut, A.; Salvini-Plawen, L. V. (Zootaxa, 2006)
A new species of Solenogastres from the Rockall Basin (NW of Scotland) at 1270 m is described. The organisation of Rhopalomenia glandulosa spec. nov. coincides with that of the type species R. aglaopheniae (Kowalevsky & Marion, 1887) in the presence of two different types of foregut glandular organs (characterised as type A or extraepithelial and type C or intraepithelial). Compared with other Rhopalomeniidae, this condition is generic and leads to the restoration of the currently synonymised genus Entonomenia Leloup, 1948, which has glandular organs consisting of ducts with subepithelially/extraepithelially arranged glandular cells only (= type A ). Besides E. atlantica Leloup, 1948 (type species), six species described as Rhopalomenia are transferred to Entonomenia.